Rheological properties and visual cohesiveness of soy protein-based formulations without thickening agents in dysphagic management - Varanya Techasukthavorn; Jirarat Anuntagool (Food Hydrocolloids for Health, 2025)
Thickened fluids, or dysphagic drinks, are commonly prescribed for individuals with swallowing difficulties. They help slow down food bolus in the swallowing process, reducing the risk of choking and aspiration. The main goal of this study was to create a set of high-protein supplement drinks varying in caloric density level. Besides, the study aimed to examine both shear and extensional rheological properties along with visual cohesiveness. Soy protein-based formulations A to F were developed with caloric densities: 1, 1.2, 1.5, 2, 2.5, and 3 kcal/mL, respectively. Each formulation was assessed through the International Dysphagia Diet Standardisation Initiative (IDDSI) flow test, shear and extensional rheological behavior, and visual cohesiveness. All samples exhibited shear-thinning behavior with viscosity increased with higher caloric density. Formulations A and B were classified as low-viscosity liquids, while formulations C, D, E, and F were suitable for extensional flow measurements with extensional properties improving as density increased. Visual cohesiveness, assessed through elongation shape and flow behavior, enhances with formulation concentration. Formulations A and B may require the addition of thickening agents to serve as thickened nutritional supplements for dysphagia management. Formulations C, D, and E were mildly to moderately thick, whereas formulation F, characterized by extremely thick with very high yield stress, may cause multiple swallows. These findings highlight the potential for developing higher-calorie supplements without thickeners as a practical strategy to enhance energy and protein intake in individuals with dysphagia. To ensure safe swallowing, future research should validate these results using in-vitro throat models and clinical studies.